Selection of environmentally safe open-pit technology for mining water-bearing deposits - Sobko, B.; Drebenstedt, C.; Lozhnikov, O. (Розробка родовищ, 2017)
Purpose. Substantiation of environmentally acceptable technologies for surface mining of water-bearing placer deposits, taking into account the parameters of mining systems elements and areas damaged during mining of mineral deposits. Findings. To conduct the research, we proposed to use index Δ which compares the actual position of inter-ramp angles and the inside dump angles with the maximum permitted values. The dependences of concentration degree KK and area of workings Str on index Δ allow to infer that the technological scheme with a rotary excavator is more environmentally sound than the scheme with hydraulic excavators. Application of the former technological scheme makes it possible to reduce the area of disturbed lands by 8%. In the proposed scheme of mining Motronivske placer deposit, the concentration degree KK reaches the maximum value 0.7, which corresponds to the minimum area of workings. Мета. Обґрунтування екологічно безпечних технологій відкритої розробки обводнених розсипних родовищ з урахуванням параметрів елементів систем розробки і площ порушених земель при видобутку корисних копалин. Результати. Під час виконання досліджень запропоновано показник Δ, який оцінює існуюче положення кутів укосів робочого борту та внутрішнього відвалу з максимально допустимими значеннями. Залежність показників ступеня концентрації КК та площі гірничих виробок від показника Δ дозволяє визначити, що технологічна схема з застосуванням роторного екскаватора є більш екологічно безпечною, ніж схема з гідравлічними екскаваторами. Використання даної схеми дозволяє зменшити площу порушених земель відкритими роботами на 8%. При цій технологічній схемі розробки Мотронівського родовища ступінь концентрації КК досягає максимального значення 0.7, що відповідає мінімальній площі гірничих виробок. Цель. Обоснование экологически приемлемых технологий открытой разработки обводненных россыпных месторождений с учетом параметров элементов систем разработки и площадей земель, нарушаемых при добыче полезного ископаемого. Результаты. При выполнении исследований предложен показатель Δ, который сравнивает существующее положение углов откосов рабочего борта и внутреннего отвала с максимально допустимыми значениями. Зависимость показателей степени концентрации KK и площади горных выработок Str от индекса Δ позволяет определить, что технологическая схема с применением роторного экскаватора более экологически безопасна, чем схема с гидравлическими экскаваторами. Применение данной схемы позволяет уменьшить площадь нарушенных земель открытыми работами на 8%. При этой технологической схеме разработки Мотроновского месторождения степень концентрации KK достигает максимального значения 0.7, что соответствует минимальной площади горных выработок.